The Impact of Individual Entrepreneurial Orientation and Self-Efficacy on Entrepreneurial Action: A Study of The Central Java Exporters Association - Mahmuda, Mahmuda; Hidayat, Yusmar Ardhi; Zaenuddin, Achmad (RSF Conference Series: Business, Management and Social Sciences, 2025)
This study investigates the impact of Individual Entrepreneurial Orientation (IEO) and Entrepreneurial Self-Efficacy (ESE) on Entrepreneurial Action (EA) among members of the Indonesia Exporters Association (IEA/GPEI) in Central Java. Acknowledging entrepreneurs as key drivers of economic growth, the research addresses the persistent challenge of business sustainability in Indonesia, where the number of entrepreneurs fluctuates. It highlights IEO (risk-taking, innovativeness, proactiveness) and ESE (belief in one's capacity to execute specific actions) as crucial internal factors for entrepreneurial success, drawing on effectuation theory to explain adaptive decision-making in dynamic environments. The research employed a quantitative approach, surveying 115 active GPEI members, predominantly young female entrepreneurs in the food and beverage sector. Using Partial Least Squares (PLS) for data analysis, the study confirmed both hypotheses: IEO has a significant positive influence on EA, and ESE also has a significant impact on EA. IEO demonstrated a stronger practical effect (medium effect size) on entrepreneurial action compared to ESE (small effect size). The findings corroborate effectuation theory, suggesting that high self-efficacy and strong orientation encourage entrepreneurs to adopt flexible, experimental effectual logic amidst uncertainty. This study contributes to the empirical understanding of psychological traits influencing entrepreneurial outcomes among early-stage exporters in Central Java, emphasizing the need for targeted capacity-building programs to strengthen entrepreneurial competencies.